The Impact of the Israeli Transplantation Law on the Socio‐Demographic Profile of Living Kidney Donors. Issue 4 (3rd March 2015) - Boas, H.; Mor, E.; Michowitz, R.; Rozen‐Zvi, B.; Rahamimov, R.
Abstract: The Israeli transplantation law of 2008 stipulated that organ trading is a criminal offense, and banned the reimbursement of such transplants by insurance companies, thus decreasing dramatically transplant tourism from Israel. We evaluated the law's impact on the number and the socio‐demographic features of 575 consecutive living donors, transplanted in the largest Israeli transplantation center, spanning 5 years prior to 5 years after the law's implementation. Living kidney donations increased from 3.5 ± 1.5 donations per month in the pre‐law period to 6.1 ± 2.4 per month post‐law (p < 0.001). This was mainly due to a rise in intra‐familial donations from 2.1 ± 1.1 per month to 4.6 ± 2.1 per month (p < 0.001). In unrelated donors we found a significant change in their socio‐demographic characteristics: mean age increased from 35.4 ± 7.4 to 39.9 ± 10.2 (p = 0.001), an increase in the proportion of donors with college level or higher education (31.0% to 63.1%; p < 0.001) and donors with white collar occupations (33.3% to 48.3%, p = 0.023). In conclusion, the Israeli legislation that prohibited transplant tourism and organ trading in accordance with Istanbul Declaration, was associated with an increase in local transplantation activity, mainly from related living kidney donors, and a change in the profile of unrelated donors into an older, higher educated, white collar population. Abstract : Using living kidney donor data collected at Israel's largest transplantation center, this study demonstrates that criminalization of organ trading by the Israeli transplantation law increased local transplantation activity, mainly from related living kidney donors, and transformed the profile of unrelated donors into an older, higher educated, white‐collar occupation population.